The effect of step count on pain and quality of recovery after cholecystectomy: a prospective observational cohort study - Cetin, Busra; Yuceler Kacmaz, Hatice; Dal, Fatih (Frontiers in Surgery, 2026)
AimThe study was conducted to determine the effect of postoperative step count on pain and quality of recovery in patients undergoing cholecystectomy.MethodThis prospective observational cohort study was conducted with 136 patients who underwent cholecystectomy at a university hospital between October 2023 and July 2024. Preoperatively, patients' information was obtained, and a 6-minute walking test was performed. Postoperatively, the number of step counts recorded by the pedometer and pain levels assessed by the Visual Analog Scale were monitored for three days. On postoperative day three, the patients were administered Quality of Recovery-15 (QoR-15). Data were analyzed using descriptive statistics, Pearson correlation analysis, and multivariable linear regression.ResultsAfter cholecystectomy, the median postoperative step count was 245 on day 1, 719.50 on day 2, and 983.50 on day 3. Mean pain scores were 7.20 ± 1.10 on postoperative day 1, 5.26 ± 1.29 on day 2, and 3.76 ± 1.42 on day 3. On postoperative day 3, the mean total QoR-15 score was 124.75 ± 18.71. Postoperative step counts were negatively correlated with pain scores and positively correlated with total and subscale QoR-15 scores. In multivariable linear regression analysis, postoperative recovery quality was independently associated with surgical approach, step count on postoperative day 3, and pain level on postoperative day 3. Higher step counts on postoperative day 3 were associated with higher QoR-15 scores, whereas higher pain levels were associated with lower QoR-15 scores.ConclusionThe findings indicate that increased postoperative physical activity is associated with reduced pain and improved quality of recovery after cholecystectomy, highlighting the importance of maintaining postoperative mobility as part of perioperative care.